2016
DOI: 10.1080/09540105.2016.1230600
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and anti-inflammatory effect of the chelate ofFlammulina velutipespolysaccharide with Zn

Abstract: The optimal conditions for preparing Zn-Flammulina velutipes polysaccharide (Zn-FVP) chelate were studied by using L 9 (3 4) orthogonal test. The results showed that the optimized conditions for the chelating reaction were as follows: initial concentration of Zn (II), 6 mg/mL; ratio of purified polysaccharide (FVPp) to Zn (II), 1:2; chelating time, 8 h; and pH, 5. Chelating rate achieved 98.11% under the optimal conditions. Characteristic bands for OH stretching at 3000-3500 cm −1 and bands corresponding to C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…It is in good agreement with the previous comparative studies on antioxidant activity of plant extracts (Debnath et al, 2011;Samad et al, 2014). LPS stimulates macrophages to produce NO and inflammatory cytokines as well (Zhao, Li, Chen, Hu, & Zhao, 2017). The effect of LSW on the viability of RAW 264.7 cells was examined by the MTT method.…”
Section: Resultssupporting
confidence: 90%
“…It is in good agreement with the previous comparative studies on antioxidant activity of plant extracts (Debnath et al, 2011;Samad et al, 2014). LPS stimulates macrophages to produce NO and inflammatory cytokines as well (Zhao, Li, Chen, Hu, & Zhao, 2017). The effect of LSW on the viability of RAW 264.7 cells was examined by the MTT method.…”
Section: Resultssupporting
confidence: 90%
“…Zhao et al . found that the combination of Zn and purified polysaccharide could change the immunoactivity of this polysaccharide, and exhibited its anti-inflammatory effect through inhibition of inflammatory cytokines release including IL-6, TNF-α, INF-γ and NO 33 . In this study, we demonstrated that FVPB2 had a pronounced stimulatory effect on the activation and immunoglobulin production of B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Follicular inductive sites in the intestine are rich in cytokines with IgA-inducing functions, including transforming growth factor β (TGF-β) and interleukin 17 (IL-17) (Cerutti & Rescigno, 2008). On the other hand, zinc is known to modulate some immunological parameters in vitro (Zhao, Li, Chen, Hu, & Zhao, 2016) and in broilers has a positive effect on the immunological capacity by improving the levels of immunoglobulins IgA, IgM, and IgG (Vieira et al, 2013). Zinc supplementation decreases oxidative stress markers and increases phagocytosis, Moreover, Zn promotes monocyte adhesion to endothelial cells in vitro and is important for the production of pro-inflammatory cytokines (Bonaventura, Benedetti, Albarède, & Miossec, 2015).…”
Section: Introductionmentioning
confidence: 99%